War Metaphors in Political Communication on Covid-19 - Castro Seixas, Eunice (Frontiers in Sociology, 2021)
Although militaristic metaphors have been pervasive during health crisis in political and science communication, few works have examined how these linguistic devices may influence crisis communication. Drawing on critical discourse analysis (CDA) and on crisis communication literature, I show how political representatives have used the war metaphor for very different purposes in terms of crisis communication and management of the current Covid-19 pandemic. I suggest that these findings challenge previous criticisms of the war metaphor as inherently negative and damaging. Finally, I discuss possibilities of using CDA, and specifically, critical metaphor analysis to inform and expand both crisis communication and management and political communication studies.